Wearable Technologies: A New Way to Address Student Anxiety. (3rd July 2022) - Johnson, Jesse; Conderman, Greg; Van Laarhoven, Toni; Liberty, Lisa
Abstract: This article provides an overview of wearable technology devices that measure physiological markers associated with stress and their use with children and youth. Tips for teachers and educational team members regarding their use are provided.